Ascending Aortic Dimensions in Former National Football League Athletes. (November 2017) - Gentry, James L.; Carruthers, David; Joshi, Parag H.; Maroules, Christopher D.; Ayers, Colby R.; de Lemos, James A.; Aagaard, Philip; Hachamovitch, Rory; Desai, Milind Y.; Roselli, Eric E.; Dunn, Reginald E.; Alexander, Kezia; et al.
Abstract : Background—: Ascending aortic dimensions are slightly larger in young competitive athletes compared with sedentary controls, but rarely >40 mm. Whether this finding translates to aortic enlargement in older, former athletes is unknown. Methods and Results—: This cross-sectional study involved a sample of 206 former National Football League (NFL) athletes compared with 759 male subjects from the DHS-2 (Dallas Heart Study-2; mean age of 57.1 and 53.6 years, respectively, P <0.0001; body surface area of 2.4 and 2.1 m 2, respectively, P <0.0001). Midascending aortic dimensions were obtained from computed tomographic scans performed as part of a NFL screening protocol or as part of the DHS. Compared with a population-based control group, former NFL athletes had significantly larger ascending aortic diameters (38±5 versus 34±4 mm; P <0.0001). A significantly higher proportion of former NFL athletes had an aorta of >40 mm (29.6% versus 8.6%; P <0.0001). After adjusting for age, race, body surface area, systolic blood pressure, history of hypertension, current smoking, diabetes mellitus, and lipid profile, the former NFL athletes still had significantly larger ascending aortas ( P <0.0001). Former NFL athletes were twice as likely to have an aorta >40 mm after adjusting for the same parameters. Conclusions—: Ascending aortic dimensions were significantly larger in a sample of former NFL athletes after adjusting for their size, age, race, and cardiac risk factors. Whether this translates to an increased risk is unknown and requires further evaluation. Abstract : Supplemental Digital Content is available in the text.